The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s1041610214001641
|View full text |Cite
|
Sign up to set email alerts
|

Detecting alcohol problems in older adults: can we do better?

Abstract: Alcohol problems in older adults aged 65 years or over, in the United Kingdom and internationally, have risen steadily over the past decade. These are a common but underdiagnosed and under-recognized problem. A UK survey in 2008 found that 21% of men and 10% of women aged 65 years and over reported drinking more than four and three units of alcohol respectively on at least one day per week (National Health Service Information Centre, 2010). A recent Royal College of Psychiatrists Report (2011) cited research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…This finding corroborates the conclusion of Taylor et al (2014) that standardized instruments have problems in identifying people with alcohol use disorders in older adults. In addition to some diagnostic criteria not being applicable to older adults, older adults may no longer recognize or remember their own adaptation processes leading to tolerance – a core diagnostic criterion of alcohol dependence.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This finding corroborates the conclusion of Taylor et al (2014) that standardized instruments have problems in identifying people with alcohol use disorders in older adults. In addition to some diagnostic criteria not being applicable to older adults, older adults may no longer recognize or remember their own adaptation processes leading to tolerance – a core diagnostic criterion of alcohol dependence.…”
supporting
confidence: 92%
“…The role of standardized instruments in identifying older adults with alcohol problems Taylor et al (2014) raise an important issue concerning the detection of alcohol problems in older adults. The authors identify a number of age-related factors playing a role in the detection of alcohol problems, such as stigma, the concept of alcohol use disorder diagnoses and their standardized assessment, and drinking levels.…”
Section: E T T E R Doi:101017/s1041610216001587mentioning
confidence: 99%
“…We found that the proportion of respondents with alcohol conversations decreased with age. In contrast, previous research and national data indicates that older adults are more susceptible to negative health consequences of alcohol, and see their primary care physician more frequently than younger adults, thus creating more reasons and more opportunities for addressing alcohol [ 30 , 31 ]. This is in line with evidence indicating a higher threshold for initiating alcohol conversations with older adults [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients over 60 years of age are more vulnerable to alcohol and are therefore at greater risk of harming their health by using alcohol, for reasons of physiological age changes, other medical conditions and use of medication (26).…”
Section: The Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…It is therefore a strength of the study that as many as 45 per cent of participants were recruited from other wards than the Emergency Department's observation and treatment ward. Interventions based on the relevance of alcohol to the patient's health problem appear to be particularly useful to the elderly, due to their reduced tolerance to alcohol, a greater number of relevant clinical issues and more frequent contact with the health service (26,29).…”
Section: The Strengths and Weaknesses Of The Studymentioning
confidence: 99%